Heterogeneous reservoir prediction of ultra-deep strike-slip fault-damaged zone constrained with local seismic anomaly data - Li, Xiangwen; Li, Jingye; Feng, Xukui; Dan, Guangjian; Zhang, Gulan; Zhang, Lei; Zhang, Ming; Zhang, Liangliang; Zhou, Hongbo; Zhao, Wei (Earth science informatics, 2022)
The fractured-vuggy reservoirs (FVRs) wrapped in strike-slip fault-damaged zones (SSFDZs) are the main drilling targets for oil-gas exploration in the Tarim Basin. The seismic characteristics of the FVRs are strong wave crest, strong wave trough, chaotic waveform and the random combination of these three types of waveforms, which are distributed in strips. Constrained sparse pulse inversion (CSSI) results based on the traditional relatively homogeneous low frequency impedance model (LFIM) cannot characterize heterogeneous FVRs. To solve this bottleneck, this paper proposes the viewpoint that the SSFDZ-transformed reservoirs are geologically isochronous. A multi-iterative inversion method (MIIM) is proposed, including multi-iterative CSSI and poststack geostatistics inversion (PSGI). This method extracts the information implicit in seismic data by AI-assisted local heterogeneity and establishes an SSFDZ framework to form a heterogeneous LFIM (HLFIM). The process performs multiple iterative constrained inversion based on the HLFIM. Finally, by combining the relative impedance with the HLFIM, absolute impedance data consistent with drilling and geological understanding are obtained. The result of MIIM improves the ability to distinguish different scale FVRs features controlled by SSFDZs. The recovery rate of reservoirs with different scales in the SSFDZs of the forward geological model is 98.15%. In the FuMan area, the success rate of commercial oil and gas flow by drilling has increased from 75 to 95% in two years and has been maintained for three years. This method can be popularized and applied, and can be used as a reference for the extraction of heterogeneous information in remote sensing data.